Quantifiable Effect of Interparticle Plasmonic Coupling on Sensitivity and Tuning Range for Wavelength-Mode LSPR Fiber Sensor Fabricated by Simple Immobilization Method - Shuo Jia; Aiwen Ma; Hanpeng Dong; Shanhong Xia (Sensors, 2022)
Herein a gold nanosphere (AuNS)-coated wavelength-mode localized surface plasmon resonance (LSPR) fiber sensor was fabricated by a simple and time-saving electrostatic self-assembly method using poly(allylamine hydrochloride). Based on the localized enhanced coupling effect between AuNSs, the LSPR spectrums of the AuNS monolayer with good dispersity and high density exhibited a favourable capability for refractive index (RI) measurement. Based on the results obtained from the optimization for AuNS distribution, sensing length, and RI range, the best RI sensitivity of the fiber modified by 100 nm AuNS reached up to about 2975 nm/RIU, with the surrounding RI range from 1.3322 to 1.3664. Using an 80 nm AuNS-modified fiber sensor, the RI sensitivity of 3953 nm/RIU was achieved, with the RI range increased from 1.3744 to 1.3911. The effect of sensing length to RI sensitivity was proven to be negligible. Furthermore, the linear relationship between the RI sensitivity and plasma resonance frequency of the bulk metal, which was dependent on the interparticle plasmon coupling effect, was quantified. Additionally, the resonance peak was tuned from 539.18 nm to 820.48 nm by different sizes of AuNSs-coated fiber sensors at a RI of 1.3322, which means the spectrum was extended from VIS to NIR. It has enormous potential in hypersensitive biochemistry detection at VIS and NIR ranges.